2017
DOI: 10.1038/ncomms14400
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots of aberrant enhancer activity punctuate the colorectal cancer epigenome

Abstract: In addition to mutations in genes, aberrant enhancer element activity at non-coding regions of the genome is a key driver of tumorigenesis. Here, we perform epigenomic enhancer profiling of a cohort of more than forty genetically diverse human colorectal cancer (CRC) specimens. Using normal colonic crypt epithelium as a comparator, we identify enhancers with recurrently gained or lost activity across CRC specimens. Of the enhancers highly recurrently activated in CRC, most are constituents of super enhancers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(144 citation statements)
references
References 76 publications
(109 reference statements)
5
139
0
Order By: Relevance
“…These sites were either "gained" or "lost" in the metastatic cells relative to their matched controls. These metastasis-associated gains and losses of the H3K4me1 signal were reminiscent of those that we previously identified in the setting of primary tumor development through comparisons of primary colon tumors and normal colon tissue, known as VELs 12,13 . In distinction, we now and herein term the regions that show differential enrichment of H3K4me1 between metastatic samples and non-metastatic controls Metastatic Variant Enhancer…”
Section: The Metastatic Phenotype Of Human Osteosarcoma Is Associatedsupporting
confidence: 59%
See 1 more Smart Citation
“…These sites were either "gained" or "lost" in the metastatic cells relative to their matched controls. These metastasis-associated gains and losses of the H3K4me1 signal were reminiscent of those that we previously identified in the setting of primary tumor development through comparisons of primary colon tumors and normal colon tissue, known as VELs 12,13 . In distinction, we now and herein term the regions that show differential enrichment of H3K4me1 between metastatic samples and non-metastatic controls Metastatic Variant Enhancer…”
Section: The Metastatic Phenotype Of Human Osteosarcoma Is Associatedsupporting
confidence: 59%
“…Previous studies by our group have demonstrated that malignant transformation is accompanied by locus-specific gains and losses in enhancer activity across the epigenome. We previously termed these Variant Enhancer Loci (VELs) 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Super enhancers are found across diverse cell types [70,71,75], they contain high levels of H3K27ac, are occupied by enhancer-associated proteins, such as Mediator and RNA Pol II, they are cell type-specific, and regulate the genes controlling cell state. Tumor cells often acquire super enhancers near oncogenes [76,77], and super enhancers are also remarkably enriched for GWAS identified SNPs that associate to several common diseases [78]. Some of the training data enhancers defined in this work might reside at the super enhancers.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic marks (or epigenotype) provide information on aberrant genomic hypomethylation and occasional transcriptional silencing by hypermethylation of selected genes normally unmethylated. The epigenotype also includes chromatin alterations and dysregulation of noncoding RNAs, which are becoming increasingly apparent threats for genome stability and significant contributors to initiation and progression of colorectal and noncolorectal carcinogenesis . Two facts in favor of the carcinogenic importance of epigenetic DNA modifications are that eventually all CRC contain a methylome characterized by hundreds to thousands of prominently aberrant methylated genes, and that more than 10% of the protein‐coding genes exhibit alterations in their methylation status .…”
Section: Melatonin and Epigenome: The Fight Against Crc In The New Eramentioning
confidence: 99%
“…The epigenotype also includes chromatin alterations and dysregulation of noncoding RNAs, which are becoming increasingly apparent threats for genome stability and significant contributors to initiation and progression of colorectal and noncolorectal carcinogenesis. 260,261 Two facts in favor of the carcinogenic importance of epigenetic DNA modifications are that eventually all CRC contain a methylome characterized by hundreds to thousands of prominently aberrant methylated genes, and that more than 10% of the protein-coding genes exhibit alterations in their methylation status. 262 Accumulated evidence indicates that epigenetic aberrations robustly influence either the prognosis and therapeutic responses of the CRC patients, such as has been reported for the radiosensitivity of human HTC116 CRC cells.…”
mentioning
confidence: 99%